Hydraulic properties and drought response of a tropical bamboo (Cephalostachyum pergracile) - Kongjarat, Wanwalee; Han, Lu; Aritsara, Amy Ny Aina; Zhang, Shu-Bin; Zhao, Gao-Juan; Zhang, Yong-Jiang; Maenpuen, Phisamai; Li, Ying-Mei; Zou, Yi-Ke; Li, Ming-Yi; Li, Xue-Nan; Tao, Lian-Bin; et al. (Plant diversity, 2024)
Bamboo plants are an essential component of tropical ecosystems, yet their vulnerability to climate extremes, such as drought, is poorly understood due to limited knowledge of their hydraulic properties. , a commonly used tropical bamboo species, exhibited a substantially higher mortality rate than other co-occurring bamboos during a severe drought event in 2019, but the underlying mechanisms remain unclear. This study investigated the leaf and stem hydraulic traits related to drought responses, including leaf-stem embolism resistance (P ; P ) estimated using optical and X-ray microtomography methods, leaf pressure-volume and water-releasing curves. Additionally, we investigated the seasonal water potentials, native embolism level (PLC) and xylem water source using stable isotope. We found that . exhibited strong resistance to embolism, showing low P , P , and turgor loss point, despite its rapid leaf water loss. Interestingly, its leaves displayed greater resistance to embolism than its stem, suggesting a lack of effective hydraulic vulnerability segmentation (HVS) to protect the stem from excessive xylem tension. During the dry season, approximately 49% of the water was absorbed from the upper 20-cm-deep soil layer. Consequently, significant diurnal variation in leaf water potentials and an increase in midday PLC from 5.87 ± 2.33% in the wet season to 12.87 ± 4.09% in the dry season were observed. In summary, this study demonstrated that the rapid leaf water loss, high reliance on surface water, and a lack of effective HVS in . accelerated water depletion and increased xylem embolism even in the typical dry season, which may explain its high mortality rate during extreme drought events in 2019.